Effects of active isolated stretching on exercise-induced muscle damage in untrained subjects: a randomized controlled trial - Muhammad Mustafa Qamar; Muhammad Shahid Javed; Muhammad Zahoor Ul Hassan Dogar; Ayesha Basharat (Journal of the Pakistan Medical Association, 2020)
Objective: To investigate the prophylactic effect of the active isolated stretching technique on exercise-induced muscle damage of wrist flexors. Method: The mixed model randomised controlled interventional study was conducted at the University of Sargodha, Sargodha, Pakistan, from November 2018 to May 2019, and comprised young adults who were untrained, sedentary and healthy who were randomly divided into intervention group A and control group B. Group A participants received self-assisted active isolated stretching before inducing muscle soreness of wrist flexors by eccentric exercises. Group B did not receive any intervention. The outcome measures were pain intensity, muscle soreness, pressure pain threshold, range of motion, and grip strength. Data were collected at baseline, after one hour, and daily from day 1 to 7 after inducing muscle soreness. Data were analysed using SPSS 21. Results: Of the 60 subjects, there were 30(50%) in each of the two groups. There were 14(23.3%) males and 46(76.7%) females. The overall mean age was 21.47±1.9 years. Group A showed early recovery in pain and muscle soreness compared to group B (p<0.05). Also, a limited deficit in the range of motion, grip strength, and pain pressure threshold was found in group A compared to group B (p<0.05). Conclusion: Active isolated stretching before strenuous, unaccustomed exercise was found to be useful in ameliorating the symptoms of muscle soreness. Key Words: Active isolated stretching, Muscle soreness, Exercise-induced muscle damage, Eccentric exercises. Continuous...